PROSES LEGALITAS GURU DAN UNIT TPA/TKA BKPRMI BERBASIS KOMUNIKASI KOLABORATIF DI KABUPATEN OGAN ILIR (STUDI PADA TPA/TKA KECAMATAN INDRALAYA DAN INDRALAYA UTARA) - Muhaimin, Ahmad; Farid, M. Mifta; Afriany, Deany; Juainah, Norma (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2025)
This study discusses the legalization process of teachers and TPA/TKA BKPRMI units based on collaborative communication in Ogan Ilir Regency, specifically in Indralaya and North Indralaya Districts. This study uses the theory of "communicative action" by Jürgen Habermas. This theory emphasizes that communication that is free from manipulation and is consensus-oriented can build mutual trust, transforming individual interactions into effective collective collaboration. This study uses a qualitative research method with a case study approach involving the Ministry of Religious Affairs of Ogan Ilir Regency, the People's Welfare Section of Ogan Ilir Regency, DPK BKPRMI administrators, and TPA/TKA institutions. Data were collected through interviews and observations. Data were analyzed using an interactive model consisting of three stages: data condensation, data display, and drawing conclusions. Active involvement between teachers, unit administrators, and related parties plays an important role in accelerating the legalization process, from administrative processing to the issuance of operational permits. The collaborative approach encourages effective coordination, transparency, and mutual trust so that bureaucratic challenges can be overcome together. The results of this study indicate that collaborative communication in the Legalization Process for Teachers and TPA/TKA Units of the BKPRMI in Ogan Ilir Regency has been successful in realizing community empowerment. This collaboration enables more effective problem-solving in the legalization process for teachers and units and can also improve the quality of early childhood religious education services in the area.